Reproduksi Sehat, Remaja Sehat di Posyandu Remaja Pashmina - Miftachul Jannah; Pedvin Ratna Meikawati; Swasti Artanti (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2021)
Adolescents are people aged 12 to 24 years. Adolescence is a transition from childhood to adulthood. This means that the process of introduction and knowledge of reproductive health has actually started at this time. In simple terms, reproduction comes from the word "re" which means to return and "production" which means to make or produce. Reproductive health, as part of general health, is thus also a human right of every person, both men and women. Women's human rights are regulated in Law Number 39 of 1999 concerning Human Rights Article 3 paragraph (3) which states that everyone has the right to the protection of human rights and human freedoms without discrimination. Reproductive health according to Law Number 36 Year 2009 is a complete physical, mental and social condition, not merely free from disease or disability related to the reproductive system, function and process in men and women. The purpose of this community service is to provide reproductive health education about healthy reproduction, healthy adolescents, especially about anemia in adolescents, reproductive health and free sex in adolescents. Methods of reproductive health counseling carried out are (1) Socialization and licensing, (2) Conducting reproductive health counseling, (3) Evaluation of the results of reproductive health counseling activities by means of pre and post tests. The results of the reproductive health counseling activity showed high enthusiasm, indicated by the very good response of participants in receiving material on healthy reproduction, healthy adolescents and the willingness of participants to ask questions. The enthusiasm of the participants is expected to increase the understanding of girls and boys about the importance of healthy reproduction, healthy adolescents.